Acceptability of immediate sequential bilateral cataract surgery (ISBCS) in a public health care setting before and after COVID-19: a prospective patient questionnaire survey. Issue 1 (9th September 2020) - Shah, Vishal; Naderi, Khayam; Maubon, Laura; Jameel, Ashmal; Patel, Darshak S; Gormley, Jack; Heemraz, Sanjeev; Azan, Elodie; Verma, Seema; Low, Sancy; O'Brart, David
Abstract : Objective: To ascertain patient acceptance of immediate sequential bilateral cataract surgery (ISBCS) in the National Health Service (NHS). Methods: A survey was devised using a 5-point Likert scale for questions related to ISBCS, which patients undertook during their cataract outpatient appointment pre-COVID-19 lockdown and by telephone during the lockdown. Results: Questionnaires were completed for 267 patients. Most respondents were aged over 71 (51%) and were female individuals (60%). Forty-five per cent agreed/strongly agreed with opting for ISBCS. A positive correlation was identified between opting for ISBCS and convenience to the patient ( r =0.76, p<0.01) and family/carer/partner ( r =0.71, p<0.01) and wanting to limit numbers of hospital visits (r=0.57, p<0.01). Fifty per cent agreed/strongly agreed that they were worried about the risk of simultaneous bilateral ocular complications, with this correlating with being less likely to opt for ISBCS ( r =−0.49, p<0.01) and being scared of ISBCS ( r =0.67, p<0.01). During COVID-19 lockdown, patients were less likely to want to minimise the time taken off work (p<0.05) and less intolerant of a prolonged hospital visit (p<0.05). Only 23% of respondents agreed/strongly agreed that they had familiarity with ISBCS. Conclusions: ISBCS was acceptable to 45% of our sampled population, suggesting limited routine implementation in the NHS is possible. Convenience and reduction in hospital visits appeared to contribute to this acceptance. Half of the patients expressed concern regarding bilateral complications and such concerns need addressing. Some attitudes did appear to change during the COVID-19 lockdown period. The familiarity of the concept of ISBCS is low suggesting the need for patient education.